2010
DOI: 10.1002/cphc.201000391
|View full text |Cite
|
Sign up to set email alerts
|

From Adlayer Islands to Surface Alloy: Structural and Chemical Changes on Bimetallic PtRu/Ru(0001) Surfaces

Abstract: The correlation between structural and chemical properties of bimetallic PtRu/Ru(0001) model catalysts and their modification upon stepwise annealing of a submonolayer Pt‐covered Ru(0001) surface up to the formation of an equilibrated PtxRu1−x/Ru(0001) monolayer surface alloy was investigated by scanning tunneling microscopy and by the adsorption of CO and D2 probe molecules. Both temperature‐programmed desorption and IR measurements demonstrate the influence of the surface structure on the adsorption properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…For instance, specific structural elements that are present only in low concentrations in the final surface may appear in much higher concentrations during the structure formation process, allowing a better identification of their structure and of their electronic/chemical properties, which in turn may be important for the understanding of the properties of the final surface. The wealth of information available had been demonstrated, for example, for the formation of PtRu/Ru(0001),8 PtCu/Cu(111),9 PtCu/Pt(111)1012 and PdAg/Pd(111)13, 14 surface alloys.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, specific structural elements that are present only in low concentrations in the final surface may appear in much higher concentrations during the structure formation process, allowing a better identification of their structure and of their electronic/chemical properties, which in turn may be important for the understanding of the properties of the final surface. The wealth of information available had been demonstrated, for example, for the formation of PtRu/Ru(0001),8 PtCu/Cu(111),9 PtCu/Pt(111)1012 and PdAg/Pd(111)13, 14 surface alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize edge effects, the surface was annealed at 700 K after Pt deposition, which leads to island sizes of 10-20 nm at 0.2 ML Pt and larger at higher coverages, respectively. [15]…”
Section: Introductionmentioning
confidence: 99%
“…12,21 STM images reveal that the concentration of defects such as step edges and kinks appears similar to those found on single crystal surfaces of Pt and Ru. 21 Infrared studies comparing low temperature adsorption of CO on Pt/Ru(0001) annealed at 700 K to PtRu/Ru(0001) NSAs annealed at 1300 K have been conducted previously. These studies showed bands consistent with CO adsorbed at the undercoordinated edge sites of the Pt islands following small CO exposures on the low temperature annealed surface, whereas the fully intermixed PtRu NSA formed by annealing to ∼1300 K only showed bands consistent with CO adsorption on Pt sites after fully saturating the surface alloy with CO. 21 This provides further evidence for the low concentration of defect sites of the intermixed PtRu/ Ru(0001) NSA.…”
Section: Introductionmentioning
confidence: 65%